Hide Information Using Plain Drawing - Kasto, Nadia (Iraqi Journal of Science, 2025)
This paper presented the development and implementation of a steganographic method, the secret message is hidden in plain drawing (AutoCAD drawing) with vector coordinate used as stego cover. This paper focuses on trading a few least significant bits of original floating-point values and replacing them with a secret text. A secret text is implemented by transform each character in the text into numbers (using RSA algorithm), then stores it as part of floating-point numbers embedded with plain drawing. The main goal of steganography was fulfilled since changing plain drawing did not drown any suspicion; the same drawing can be used by experimental person and does not alter the original data content.